Examining the Students’ Vocabularies Improvement by Using Scramble Card - Palupi, Risqi Ekanti Ayuningtyas; Sunardi, Andhina Ika; Cahyono, Dwi (Siliwangi University, 2024)
This research is aimed at whether using scramble cards improves the students’ vocabulary. It is also aimed at the enrichment of the students’ achievement in teaching learning process using scramble cards. The materials used in this research were scramble cards. Some steps in this research start from identifying the problems, planning the action, implementing the action, observing or monitoring the action, reflecting the result of the observation, and research findings. The research was conducted in four meetings. A meeting for pre-test, 2 meetings for treatments and a meeting for post-test. The sample of this research was 35 first-year students of a polytechnic in Indonesia. The technique in collecting the data was quantitative method. In the quantitative method, the researcher used tests to examine the students’ achievement. The test consisted of the pre-test and post-test. The technique to analyze the test result was by comparing the mean score of pre-test and post-test. Besides that, this research also used descriptive statistics and the t-test of non-independent. The research result shows that scramble card can enhance the students’ vocabulary mastery, it can be seen from the aspect of the vocabulary mastery, such as the students could understand, grasp, remember, pronounce, write about 80 until 90 % of the words correctly and use the words in some sentences appropriately. Second, the improvement also can be seen from the pre-test and post-test of the students’ score. The mean score of the pre-test improves from 5.67 to 8.85 in post-test. Then, the scores of the pre-test and post-test show that there is also an improvement in students who achieve the minimum standard score, that is 60. They are from 3.2% to 100% of students. As the conclusion of this research that the use of scramble cards improves students’ vocabulary mastery.Keywords: vocabulary, scramble card, classroom action-research, improvement